Leaf Area and Stomata Index of Rice Plants (Oryza sativa L.) Cisokan and Batang Piaman Varieties to Drought Stress - Putri Widianti; Violita Violita; Moralita Chatri (Bioscience, 2017)
Background and objective.The response of rice plants to drought stress was preceded by physiological response in the form of reduction of transpiration rate to reduce water loss by closing stomata, reducing stomata, and decreasing leaf surface area by leaf rolling. Therefore, it is necessary to research the morphological character and physiological character of plants such as leaf area analysis and stomata index to find out their response to drought stress and without drought. Based on this, this research is aimed to know the area and index of stemata leaves of rice plants (Oryza sativa L.) varieties of Cisokan and Batang Piaman due to drought stress.Methodology. Drought treatment was performed by withholding water for 12 days in greenhouse.Data were taken destructively on days 0, 4, 6 and 12 after treatment. Result. Drought stress had an effect on decreasing leaf area and stomata index on both varieties. The lowest leaf area is found in Cisokan variety. Likewise with the stomata index, the lowest yield after 12 days of treatment was found in the Cisokan variety. Low leaf area and stomatal index are known to be more resistant to drought because they can reduce the rate of transpiration in plants. Keywords:    Drouhgt stress, Leaf Area, Stomata index